Head and Spinal Trauma Management in Disaster - Baş, Gülçin; İşler, Cihan; Kemerdere, Rahşan; Hancı, Mehmet Murat (Cerrahpaşa Medical Journal, 2023)
Traumatic brain and spinal injuries are important causes of death and morbidity. Although trauma is a significant medical entity for mortality and morbidity in all age groups worldwide, it is a prominent cause of death and morbidity, especially under the age of 45. Apart from the main causes of multitrauma, natural disasters are also an important and devastating cause of mortality and morbidity and can present a major threat to individual and public health. Appropriate organization and implementation of trauma management should be performed in these scenarios as well to assure that a large-scale medical aid arrives to the scene Cite this article as: Baş G, İşler C, Kemerdere R, Hancı MM. Head and spinal trauma management in disaster. Cerrahpaşa Med J 2023;47(S1):54-61.